FLOWERING INTENSITY AND FLOWER VISITORS OF Santalum album L. AT EX-SITU CONSERVATION PLOT, WATUSIPAT, GUNUNG KIDUL, YOGYAKARTA - Liliana Baskorowati (Indonesian Journal of Forestry Research, 2011)
Flowering intensity, insects visiting flowers and pollinators of S. album were determined in a study conducted in an ex-situ conservation plot, Watusipat, Gunung Kidul, Yogyakarta. Observations were undertaken during flowering season in 2009 and 2010, with an objective to determine the patterns of flowering and flower visiting insects of S. album in this population. In this study site, S. album typically flowers twice a year and reaches a peak on June and November. Flowers are visited by various insects, major in honey bees and ants. Santalum album is predominantly cross pollinated by insects however, low number of fruit set found in an open pollination. Variation of flowering intensity and the degree of self-incompatibility may influence the low number of fruit production in this species.